A discourse analysis on the UAAP Men's Football games as reflection of the Philippines' socio-cultural context - Guno, Christia Ruth V., 1995-; Liquigan, Boots; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2017)
Sport is a key player in building a nation through its impact on a country's economy, politics, society, and education. In the Philippines, football has struggled to gain popularity, despite the Philippine National Team, the Azkals recent wins. Media has played a major role in making sports accessible and popular to audiences and even in influencing the audience's interpretation and meaning making through framing. The media texts of the televised UAAP Men's Football games were analyzed using an integrated framework of Discourse Analysis and Media Framing Theory to shed light to the question, how does the UAAP Season 78 Football games reflect the Philippines' socio-cultural context? The research aimed to, a)to identify and analyze the texts and framing used in the coverage of the games; b)to expose the discourse within the coverage based on the textual analysis; and c)to explain Philippine socio-cultural themes present in the UAAP men's football games. The results questioned the power of media to impact the popularity of the sport and challenges the identity of Filipino culture.
Vita.
Thesis (A. B. Broadcast Communication)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Football -- Dsicourse analysis -- Philippines; UAAP Men's Football Games